On processes determining the vertical stability of surface waters in the marginal ice zone of the north-western Weddell Sea and their relationship with phytoplankton bloom development - Veth, Cornelis; Lancelot, Christiane; Ober, S. (1992)
Ice-edge-related phytoplankton blooms following the retreating sea-ice in the marginal ice zone are frequently observed phenomena. Such blooms are generally short-lived and are followed by a strong decrease in the chlorophyll concentration towards the open ocean, generally explained by the degradation of the vertical stability. Solar heating and ice melting, which control the stability of the surface water of the north-western Weddell Sea during sea-ice retreat in spring were analysed in order to relate the spatial features of the phytoplankton ice-edge bloom in 1988 to the density field. Solar heating has little effect on the density of seawater in ice-covered areas because the thermal expansion coefficient is very low close to the freezing temperature. Outside the marginal ice zone, the temperature effect on stratification increases and the combined contribution of melting and heating on buoyancy input to the surface layer is roughly constant. As a consequence, the low phytoplankton stocks in the open ocean adjacent to the marginal ice zone, after an initial bloom peak following the retreating ice in spring, are not necessarily caused by deep turbulent mixing, in contrast to what is often assumed. Data presented here were collected during the European Polarstern Study (EPOS) sponsored by the European Science Foundation info:eu-repo/semantics/published